«Je suis encore vivant!» - Carlo Alberto Petruzzi (Mimesis Journal, 2023)
The Italian actor, film director and thinker, Carmelo Bene (1937-2002) is one of the greatest figures of Italian theatre of the XXth century. Bene made his debut in Albert Camus’ Caligula in 1959 and later presented two other versions of the play: a recital in Florence (1960) and a second edition staged in Genova in 1961, which had been until now neglected by the critic. The article focuses on the three editions of Caligula and although Bene’s later rejected the early years of his activity, it argues that it is instead possible to establish a continuity between the beginning of his career and his mature productions.